Revelation and Scripture: theological interpretation of Emerging church - Soloviy, Roman (Skhid, 2016)
The article deals that biblical theology of Еmerging church focused primarily on the issues of the role of the community in the interpretation of Holy Scripture, the characteristics of the Biblical narrative and comparison of the Bible and the Word of God. According the theology of community sources for the development of theology found in Holy Scripture, tradition and culture, through which God speaks. Therefore Holy Scripture is not the monopoly authority in matters of faith and theology. To explain Holy Scripture can only staying in the church community where truly knowable Christian truth. According B.McLaren the Bible should never be studied and analyzed. The Bible should be seen as a work of art and to read like a story based on the fact that most of the text of Holy Scripture is precisely the narrative. The cause of erroneous traditional reading of the biblical narrative is that it was generated by the synthesis of the Greek philosophical tradition (especially Neo-Platonism) with the political, economic and military dominants of Roman Empire. B.McLaren considers the correct way of understanding the Bible attitude to it as a library of specific community (or culture), which traces its history to the biblical patriarchs. The task of the modern reader of the Bible - put yourself in text, in conversation, in history, in a community of people who seek God.